Aplicación de técnicas para mejorar la lecto escritura en niños y niñas de segundo año de educación básica de La Unidad Educativa Juan E Verdesoto del Cantón Babahoyo - Yépez Barzallo, Tatiana Belén (2023)
This work aims to investigate the application of techniques to improve reading and writing in boys and girls in the second year of basic education at the Juan e Verdesoto Educational Unit of the Babahoyo Canton whose fundamental objective is to determine the factors that influence the application of learning techniques to reading and writing, the problem of which is that there are several children from early childhood to high school who have difficulty reading and writing, this is due to the fact that in the first years of learning the students did not develop reading and writing skills, nor created phonological awareness, the The methodology used is qualitative information was collected from the direct observation of 35 boys and girls in the second year of basic education at the Juan E Verdesoto Educational Unit of the Babahoyo canton. And 2 teachers from a more complex perspective, considering the techniques for learning reading and writing as a fundamental basis for the development of linguistic skills and reading comprehension, which yielded results where we were able to observe that teachers apply techniques for this process which They serve the majority of students while a small group fails to develop these skills. The Educational Unit of the Babahoyo canton of the province of Los Ríos participates in the research development, with the contribution of a theoretical framework that arises from the process of reflection and conceptual theoretical elaboration, from the analysis, experiences and participation of both teachers and students, the which led us to the conclusion that to apply techniques to improve reading writing, innovative strategies must be used that draw the student's attention and allow them to learn at their own learning pace.